2014
DOI: 10.1016/j.ijgo.2014.09.028
|View full text |Cite
|
Sign up to set email alerts
|

One‐year follow‐up of women who participated in a physiotherapy and health education program before and after obstetric fistula surgery

Abstract: Results obtained after surgery and physiotherapy were maintained at 1 year, and QoL had improved significantly. When women are encouraged to continue exercises, improvements are also seen in residual stress incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…However, our findings are nearly identical to the 20% residual incontinence prevalence reported in a multi‐country prospective study evaluating women 3 months after repair . Other studies have shown improvements in urinary incontinence from discharge to 6–12 months after surgery . It is possible that women continue to regain continence after this time period, even among women with small residual fistulas.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, our findings are nearly identical to the 20% residual incontinence prevalence reported in a multi‐country prospective study evaluating women 3 months after repair . Other studies have shown improvements in urinary incontinence from discharge to 6–12 months after surgery . It is possible that women continue to regain continence after this time period, even among women with small residual fistulas.…”
Section: Discussionsupporting
confidence: 87%
“…In other settings, quality of life has been shown to be lower in women with residual incontinence from a persistent VVF . One study found no difference in the quality of life of women with persistent fistula before and after repair but did find a difference between those with successful and unsuccessful fistula closure, regardless of urinary incontinence symptoms . Qualitative studies further characterise the ongoing distress and social limitations in women with residual incontinence .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies tested a combined health education and physiotherapy program . In Benin, Castille et al .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies tested a combined health education and physiotherapy program . In Benin, Castille et al . employed physiotherapist‐led didactic sessions to assist women in activity modification including perineal contractions, abdominal hypopressive exercise, and behavioral instruction.…”
Section: Resultsmentioning
confidence: 99%